2011
DOI: 10.1530/eje-11-0687
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes reduces left ventricular ejection fraction-irrespective of presence and extent of coronary artery disease

Abstract: Background: It is not clear whether diabetes reduces systolic left ventricular function (left ventricular ejection fraction, LVEF) irrespective of coronary artery disease (CAD). The aim of this study was to compare the LVEF between diabetic and non-diabetic patients with respect to the extent of CAD. Methods and results: Consecutive patients undergoing stress myocardial perfusion SPECT (MPS) were evaluated. MPS was interpreted using a 20-segment model with a five-point scale to define summed stress score (SSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 39 publications
(39 reference statements)
5
13
0
3
Order By: Relevance
“…The LVEF reduction is seen and reached statistical significance in type 2 diabetes. Our finding is consistent with previous reports of reduced LVEF in diabetic patients regardless of the extent of coronary artery disease [27,28]. Our study observed in a subset of patient with DM (type 2 only) that demonstrated a concomitant developmental change in QTc and LVEF with an inverse relationship.…”
Section: Discussionsupporting
confidence: 93%
“…The LVEF reduction is seen and reached statistical significance in type 2 diabetes. Our finding is consistent with previous reports of reduced LVEF in diabetic patients regardless of the extent of coronary artery disease [27,28]. Our study observed in a subset of patient with DM (type 2 only) that demonstrated a concomitant developmental change in QTc and LVEF with an inverse relationship.…”
Section: Discussionsupporting
confidence: 93%
“…DM was an important risk factor for progression from asymptomatic systolic dysfunction to symptomatic heart failure only in patients with ischemic cardiomyopathy [25]. However, Ehl et al showed that DM reduces LV ejection fraction, estimated by SPECT, irrespectively of the presence and extent of CAD and suggested that it might in part explain generally worse cardiac survival compared to non-diabetics [26]. …”
Section: Discussionmentioning
confidence: 99%
“…[16] A previous large cohort study identified that reduced LV function was significantly associated with increased 1-month and 1-year mortality risk in patients with AMI. [7] Ehl et al [17] reported that DM patients exhibited a lower LVEF than non-DM patients regardless of CAD extent and suggested that this difference was associated with worse CV mortality in DM patients. The present study found that the incidence of LVEF <35% was significantly higher in DM patients despite the absence of significant differences in the incidence of multivessel disease and type B2/C lesions between the propensity-matched populations.…”
Section: Discussionmentioning
confidence: 99%